Nigeria - Sutherland, Dorothy B. (Chicago : Childrens Press, 1995)
Discusses the geography, people, economy, and customs of this West African country.
Includes index.
6.
6.1
5-8
5-9.
Keywords: Nigeria -- Juvenile literature; Nigeria; Nigeria